2020
DOI: 10.1186/s12880-020-00428-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance 4D flow analysis has a higher diagnostic yield than Doppler echocardiography for detecting increased pulmonary artery pressure

Abstract: Background: Pulmonary hypertension is definitively diagnosed by the measurement of mean pulmonary artery (PA) pressure (mPAP) using right heart catheterization. Cardiovascular magnetic resonance (CMR) four-dimensional (4D) flow analysis can estimate mPAP from blood flow vortex duration in the PA, with excellent results. Moreover, the peak systolic tricuspid regurgitation (TR) pressure gradient (TRPG) measured by Doppler echocardiography is commonly used in clinical routine to estimate systolic PA pressure. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…A more recent, and direct, method for estimating MPAP by CMR assesses the presence and duration of vortical blood flow in the main PA (Table 1 ) [ 81 ••, 82 85 ]. A vortex is a formation of concentric ring- or spiral-shaped curves [ 86 89 ] and is an effect of coexisting forward flow and retrograde flow at the posterior wall during systole in the main PA (Fig.…”
Section: Estimates Of Mean Pulmonary Pressure and Pulmonary Resistancmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent, and direct, method for estimating MPAP by CMR assesses the presence and duration of vortical blood flow in the main PA (Table 1 ) [ 81 ••, 82 85 ]. A vortex is a formation of concentric ring- or spiral-shaped curves [ 86 89 ] and is an effect of coexisting forward flow and retrograde flow at the posterior wall during systole in the main PA (Fig.…”
Section: Estimates Of Mean Pulmonary Pressure and Pulmonary Resistancmentioning
confidence: 99%
“…A vortex is a formation of concentric ring- or spiral-shaped curves [ 86 89 ] and is an effect of coexisting forward flow and retrograde flow at the posterior wall during systole in the main PA (Fig. 1(N) ) [ 81 ••, 82 85 ]. The premises for estimating MPAP from vortex formation are (1) detection of a vortex (indicating increased resistance and decreased elastance) and (2) the time it exists in relation to the full cardiac phase (to evaluate the pressure increase).…”
Section: Estimates Of Mean Pulmonary Pressure and Pulmonary Resistancmentioning
confidence: 99%
“…Very little has been written about the use of cardiac MR to evaluate left diastolic function. Recently, Ramos et al [23,24] concluded good agreement and diagnostic yield for pulmonary hypertension and diastolic dysfunction between cardiac MR and echocardiography. This contributes to expanding the diagnostic capabilities of cardiac MR in patients with cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not possible to calculate the absolute blood pressure solely from a velocity field. Previous studies have investigated the relationship between mean PAP and velocity field [7,19,20,21]. 3D structure and coexists with helical flow, it is difficult to accurately make a visual assessment of changes in its size and duration.…”
Section: Perioperative Changes In Backward Flow and Whole Pulmonary Blood Flowmentioning
confidence: 99%
“…Reiter et al (2015)[10] observed vortices in the pulmonary trunk for patients with pulmonary hypertension, and successfully demonstrated a strong correlation between appearance time of vortices and mean PAP. Using the same technique, Ramos et al(2020)[21] demonstrated a correlation between mean PAP, estimated by the duration, and the transtricuspid pressure gradient (TRPG). Because vortical flow in the PA has a…”
mentioning
confidence: 99%